The application of live TV-link and screen for vulnerable witnesses: An overview in the Malaysian criminal justice system - Abidah Abdul Ghafar; Shah H.A.R.; Shukor S.A.; Muda R.; Saleh N.S.S.N.; Ismail F.S.M. (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA